Contemporary fisherian life-history evolution in small salmonid population - Koskinen, Mikko T; Haugen, Thrond O; Primmer, Craig R (Nature (London), 2002)
The relative importance of natural selection and random drift in phenotypic evolution has been discussed since the introduction of the first population genetic models. The empirical evidence used to evaluate the evolutionary theories of Fisher and Wright remains obscure because formal tests for neutral divergence or sensitive attempts to separate the effects of selection and drift are scarce, subject to error, and have not been interpreted in the light of well-known population demography. We combined quantitative genetic and microsatellite DNA analyses to investigate the determinants of contemporary life-history evolution in isolated populations of grayling (Thymallus thymallus, Salmonidae) that originated from a common source 80-120 years ago. Here we show that natural selection was the dominant diversifying agent in the evolution of the quantitative traits. However, the populations were founded by a small number of individuals, exhibit very low microsatellite-based effective sizes and show genetic imprints of severe 'bottlenecks'; which are conditions often suggested to constrain selection and favour drift. This study demonstrates a very clear case of fisherian evolution in small natural populations across a contemporary timescale.